Effective interventions for working with young people who are homeless or at risk of homelessness - Justin Barker
This literature review was commissioned by the Commonwealth Department of Families, Housing, Community Services and Indigenous Affairs (FaHCSIA). The aim of the review is to assess the current state of evidence about what interventions are most effective in working with young people who are homeless or at risk of homelessness. This literature review was produced in order to inform a broader project that identifies the range of interventions and strategies that are applied by Reconnect services and situates these practices within the existing evidence base (see separate report, Reconnect: working with young people who are homeless or at risk of homelessness). Reconnect is a community-based early intervention program for young people who are homeless or at risk of homelessness. It was established in 1998 as an early intervention response to youth homelessness. Reconnect uses early intervention strategies to help young people to stabilise and improve their housing, achieve family reconciliation, and improve their level of engagement with work, education, training and community. FaHCSIA funds Reconnect services to deliver services to young people aged 12–18 years (newly arrived young people 12–21 years) who are homeless or at risk of homelessness, and their families. Some Reconnect services focus on working with specific population groups, for example: Indigenous young people (Aboriginal or Torres Strait Islander people); young people experiencing mental health issues; and newly arrived young people. This review is guided by the key research question: ‘what are effective intervention strategies for working with young people who are homeless or at risk of homelessness?’ The literature review begins with a brief overview of youth homelessness as an issue of concern, its identified relevant risk and protective factors, and the relevance of early intervention. It then outlines the strategy for undertaking this literature review and presents the findings of the review